Carbon Emission Disclosure Perusahaan Non-Keuangan dalam Perspektif Teori Legitimasi dan Stakeholder - Juwantina Eka Tari; Indah Fajarini Sri Wahyuningrum (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the effect of corporate governance mechanisms on carbon emission disclosure (CED) in non-financial companies listed on the Indonesia Stock Exchange. The governance mechanisms examined include institutional ownership, audit committee, gender diversity, and media exposure, with environmental performance serving as a moderating variable. This research employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, and corporate websites for the 2022–2024 period. The research sample was selected using a purposive sampling method, while hypothesis testing was conducted using Moderated Regression Analysis (MRA). The results indicate that institutional ownership and media exposure have a positive and significant effect on carbon emission disclosure. The audit committee and gender diversity do not show a significant effect on CED. The moderating test results reveal that environmental performance is unable to strengthen the relationship between institutional ownership, audit committee, gender diversity, and media exposure to carbon emission disclosure. These findings suggest that external pressures play a more dominant role in encouraging environmental disclosure transparency than internal board characteristics. This study is expected to contribute empirical evidence to the development of environmental accounting and corporate governance literature in Indonesia.